2011
DOI: 10.1038/ismej.2011.104
|View full text |Cite
|
Sign up to set email alerts
|

Spatial distribution of microbial communities in the cystic fibrosis lung

Abstract: Cystic fibrosis (CF) is a common fatal genetic disorder with mortality most often resulting from microbial infections of the lungs. Culture-independent studies of CF-associated microbial communities have indicated that microbial diversity in the CF airways is much higher than suggested by culturing alone. However, these studies have relied on indirect methods to sample the CF lung such as expectorated sputum and bronchoalveolar lavage (BAL). Here, we characterize the diversity of microbial communities in tissu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
126
4

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 152 publications
(139 citation statements)
references
References 16 publications
9
126
4
Order By: Relevance
“…However, fermentative signals observed from CF samples were not likely from saliva contamination, because the characteristic gas bubble formation was only present during exacerbation and never at times of stability even though sampling procedures were identical. Oral bacteria have been detected before in the upper airways and sputum of CF patients (Tunney et al, 2008;Worlitzsch et al, 2009;Goddard et al, 2012;Willner et al, 2012), and our results indicate that they colonize lung mucus and may contribute significantly to exacerbations. However, it cannot be known whether these bacteria drive exacerbation onset or whether their growth is favored during the conditions of an exacerbating CF lung.…”
Section: Sources Of the Fermentative Responsementioning
confidence: 85%
“…However, fermentative signals observed from CF samples were not likely from saliva contamination, because the characteristic gas bubble formation was only present during exacerbation and never at times of stability even though sampling procedures were identical. Oral bacteria have been detected before in the upper airways and sputum of CF patients (Tunney et al, 2008;Worlitzsch et al, 2009;Goddard et al, 2012;Willner et al, 2012), and our results indicate that they colonize lung mucus and may contribute significantly to exacerbations. However, it cannot be known whether these bacteria drive exacerbation onset or whether their growth is favored during the conditions of an exacerbating CF lung.…”
Section: Sources Of the Fermentative Responsementioning
confidence: 85%
“…Notably, obligately anaerobic taxa have gained recent attention for their abundance in expectorated sputum, bronchoalveolar lavage fluid and explanted lungs [5,27,28,[32][33][34]. A role for these organisms in CF disease has not yet been established; however, some have been characterized for their ability to degrade and ferment salivary mucins in the oral cavity [21,23,35].…”
Section: Saliva-derived Mucin-fermenting Bacteria Support the Growth mentioning
confidence: 99%
“…For example, two studies identified low-diversity microbiota in explanted lungs, each dominated by one or two traditional pathogens, but relatively higher diversity microbiota in concurrent oropharyngeal and sputum samples, with sputum identifying the predominant organisms in the lung more accurately than did oropharyngeal samples (7)(8)(9). By contrast, other studies of explanted and postmortem lungs demonstrated more diverse microbiota, including anaerobes (except where specified otherwise, the word "diverse" here signifies the number of species, often referred to as "richness" in ecology) (10,11). However, because these specimens reflected end-stage CF lung disease, it is difficult to interpret the relevance of their lung microbiota findings for earlier disease.…”
mentioning
confidence: 88%
“…As the previously mentioned specimen types likely sample, and therefore reflect, both the lungs and these nonlung sources to varying degrees (7), CF microbiota studies have examined lungs collected during transplantation or postmortem (therefore representing endstage disease [7][8][9][10]), and have yielded some consistent and some divergent findings. For example, two studies identified low-diversity microbiota in explanted lungs, each dominated by one or two traditional pathogens, but relatively higher diversity microbiota in concurrent oropharyngeal and sputum samples, with sputum identifying the predominant organisms in the lung more accurately than did oropharyngeal samples (7)(8)(9).…”
mentioning
confidence: 99%